PROSPEK PENGEMBANGAN INDUSTRI MAKANAN OLAHAN PEMPEK PALEMBANG DI KOTA PEKANBARU - Yovita Permata Sahli; Azwar Harahap; Yusni Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to determine the prospects of the processed food industry businesses pempek Palembang in Pekanbaru and to investigate any problems or constraints encountered in pempek Palembang run the business in the city of Pekanbaru.The population in this study are all businesses that sell and produce pempek Palembang in the city of Pekanbaru is 10 outlets.This study took a sample of 10 outlets pempek Palembang in city of Pekanbaru. The method used in this reseach is using feasibility studies, to conduct a review of the aspects of the feasibility study that review on aspects of financial and aspects of non financial.In the aspects non-financial through reviews on aspects of the market, raw material and socio-economic,as well as a review on the financial aspects through a review of financial feasibility by performing the calculation of Net Present Value (NPV), B / C Ratio, Internal Rate of Return (IRR) and Payback Period (PP). On the results of this study indicate that non-financial aspects of the review in the processed food industry pempek Palembang in the city of Pekanbaru has a prospects and feasible to develop, and review the financial aspects through feasibility calculations show NPV =513.684.145,7> 0, the value of B / C Ratio 1,23> 1, IRR 47.04%> 12% and the value of PP for 7,99 months (0,66 years). From these calculations show that the processed food industry pempek Palembang in the city of Pekanbaru has a prospects and feasible to develop.Keywords: Prospects, Feasibility Studies, and Pempek Palembang.